Efficacy of insect growth regulator, pyriproxyfen against cotton whitefly and predatory complex on Bt cotton - Chandi, Ravinder Singh; Kumar, Vijay (Indian Journal of Plant Protection, 2020)
Pyriproxyfen 10 EC was evaluated @ 30, 40, 50 and 60 g a.i./ha against cotton whitefly and predatory complex in four different experiments on Bt cotton during 2009 and 2010. The standard check was ethion 50 EC @ 1000 g a.i./ha. Based on pooled mean of two years, the per cent reduction of whitefly adults over control in pyriproxyfen 10 EC @ 60 g a.i./ha was at par with ethion 50 EC at 10 days after spray (DAS) but was significantly inferior as compared to standard check at 3 and 7 DAS. However, all the four pyriproxyfen dosages were significantly more effective against nymphal population of whitefly after 1, 3 and 7 DAS as against standard check. After 7 days of spray, the per cent reduction in whitefly nymphs over control in pyriproxyfen 10 EC @ 50 and 60 g a.i./ha was 90.4 and 95.4 per cent, respectively. Seed cotton yield in pyriproxyfen @ 50 and 60 g a.i./ha (24.7 and 24.8 q / ha) was also higher in comparison to all other treatments. Moreover, pyriproxyfen was comparatively safer to the predatory complex.